Peran Lingkungan Madrasah Dalam Pembentukan Karakter Siswa MIM 2 Slinga Kaligondang Purbalingga - Mukharoh, Laela; Ningsih, Tutuk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The study, entitled the role of the madrasah environment in the character building of students at MI Muhammadiyah 2 Slinga kaligondang purbalingga has the aim of providing an overview of how the role of the madrasah environment can shape the character of MI Muhammadiyah 2 Slinga students. This paper is a deductive paper, the result of research with environmental research subjects at MI Muhammadiyah 2 Slinga. The results showed that the character of the students at MIMuhammadiyah 2 Slinga could be shaped by the interaction between students and stakeholders in the madrasah environment and the situation in the madrasah environment.